An update on immediate sequential bilateral cataract surgery. Issue 1 (20th January 2023) - Spekreijse, Lindsay S.; Nuijts, Rudy M.M.A.
Abstract : Purpose of review: The aim of this study was to present an overview of recent publications and opinions in the field of same-day bilateral cataract surgery. Recent findings: A Cochrane review was published comparing immediate sequential bilateral cataract surgery (ISBCS) and delayed sequential bilateral cataract surgery (DSBCS) with regard to safety outcomes, costs and cost-effectiveness. In addition, several large database studies provided more information on incidences of rare complications such as unilateral and bilateral endophthalmitis rates. Summary: Recently available evidence showed that ISBCS is an effective and cost-effective alternative to DSBCS. Nonetheless, additional (randomized) registry studies, randomized controlled trials and cost-effectiveness studies are needed to evaluate bilateral endophthalmitis rates, refractive outcomes and cost-effectiveness of ISBCS compared with DSBCS.